Anthropometric Properties versus Physical Performance in Rugby ::union:: Forwards and Backs - A Systematic Review - Rahel Stoop; Erich Hohenauer; Alfred ML Rucker; Ron Clijsen (The Society of Aging and Physical Activity (SAPA), 2018)
Background. Rugby ::::::union:::::: is a team sport with a high amount of physical contact during match play. The physical performance and anthropometric characteristics required, differ based on the playing position. Objectives. The objective of this systematic review was to relate anthropometric properties with physical performance parameters in Rugby ::::::union:::::: backs and forwards across different playing levels of Tier 1 nations. Methods. Two electronic searches were performed in MEDLINE on the PubMed and on BISp (German Federal Sports Science Institute) databases from August 2016 to July 2017. All experimental study types in English and German were assessed for eligibility. Inclusion criteria were 15-a-side senior male backs and forwards, with anthropometric and/or physical performance data. Results. In n = 7 studies out of 12 selected, the elite forwards were significantly taller than the elite backs (p < 0.05). This accounted not for lower playing levels. Across all levels the forwards were significantly heavier than the backs. Significantly lower body fat percentages for the backs demonstrated n = 5 out of 6 studies. Consequently, backs were more ectomorphic than forwards. Backs reached significantly lower sprint velocities over short distances and higher ones over longer distances (10 to 40 m). Conclusion. Anthropometric parameters adapt to physical performance requested. In strength and endurance test situations heavier players may be underestimated postulating careful interpretation of those results to avoid misleading conclusion.